The Use of YouTube Videos as Media for English Language Teaching: Personal Stories of EFL Teachers - Alvin Aula Muktisari (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
In the teaching and learning process, interesting and fun media is needed so that students do not easily feel bored with learning. Dewi et al., (2018) stated that to achieve educational goals in general and learning goals in schools in particular, it can be said that media is a very important component in the learning process because it can attract students' interest and can motivate students in learning. Nowadays, technology is increasingly advanced, including in education. Various media can be easily accessed including social media. According to Gaile (2013), the presence of social media today is seen in various ways and means of communication. There are various social media that are often encountered, including Facebook, Instagram, TikTok and YouTube. This social media can be used for learning and teaching process. However, one platform that can attract students' attention in class learning is YouTube. YouTube is a website where many types of videos are shared, including TV snippets, music videos, movie trailers, and other types of content including video blogging, short original films, and informative films (Jalaluddin, 2016). YouTube is easily accessed via the internet by all people. For education, teachers can find many sources of English teaching videos on YouTube. Students can also learn to use YouTube independently wherever they are and whenever they want to learn because YouTube is easy to access. Research related to the topic of YouTube in EFL teaching is important. YouTube is one of the most significant online tools for language learning, YouTube also a popular platform where users can create videos, share them with others, and comment on videos posted by others (Binmahboob, 2020). This study aims to find out how EFL teachers use YouTube videos in English language teaching based on stories from these teachers' teaching experiences. The research took place in Jember, with the participants of two junior high school teachers in Jember.
Reaploud Repository 13 April-agus
Keywords: Videos; YouTube; Teaching Media; EFL